To Doubt in Our Hearts: The Substance Dualism in the Light of Peirce’s Criticism of ‘the Spirit of Cartesianism’ - Risteski, Aleksandar (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
In this article, the author addresses the problem of Cartesian dualism through the prism of Peirce’s criticism of the ‘spirit of Cartesianism’. The faith in the intuitive knowledge and the strong emphasis on individualism Peirce sees as its two main features, therefore, they are the focus of the paper. The underlying idea is to show that, in the light of the pragmatic critique, the Cartesian substance dualism appears to be foremost an epistemological and methodological problem, and not a metaphysical problem of disparate substances.
Keywords: intuition; substance dualism; doubt; process; community